2016
DOI: 10.18632/oncotarget.9871
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the dynamic expression of checkpoint molecules on cytokine-induced killer cells from non-small-cell lung cancer patients

Abstract: Immune checkpoints associate with dysfunctional T cells, which have a reduced ability to clear pathogens or cancer cells. T-cell checkpoint blockade may improve patient survival. However, checkpoint molecules on cytokine-induced killer (CIK) cell, a non-specific adoptive immunotherapy, remain unknown. In present study, we detected the dynamic expression of eight major checkpoint molecules (CTLA-4, PD-1, PD-L1, TIM-3, CEACAM-1, LAG-3, TIGIT and BTLA) on CIK cells from NSCLC patients. The majority of these molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 52 publications
(72 reference statements)
2
35
0
Order By: Relevance
“…Immunotherapy is an effective strategy against tumors, and the therapeutic targets of immune checkpoint proteins include programmed death‐1 (PD‐1), TIGIT, LAG‐3, and TIM‐3; the inhibition of the described targets by their antibodies has the potential to reactivate immune system elements such as cytotoxic CD8+ T cells . The results of this study indicated that the overexpression of other immune checkpoints in the KOSC‐3‐derived tumorspheres (Table ), include PD‐L2 , Gal‐9 , HLA‐E , and CD155 .…”
Section: Discussionmentioning
confidence: 87%
“…Immunotherapy is an effective strategy against tumors, and the therapeutic targets of immune checkpoint proteins include programmed death‐1 (PD‐1), TIGIT, LAG‐3, and TIM‐3; the inhibition of the described targets by their antibodies has the potential to reactivate immune system elements such as cytotoxic CD8+ T cells . The results of this study indicated that the overexpression of other immune checkpoints in the KOSC‐3‐derived tumorspheres (Table ), include PD‐L2 , Gal‐9 , HLA‐E , and CD155 .…”
Section: Discussionmentioning
confidence: 87%
“…However, our immune system does not work effectively in the setting of malignancy. The reason for this may be the existence of immune suppression [60][61][62].…”
Section: The Changes Of Tregs and Mdscs Of Nsclc Patients In Periphermentioning
confidence: 99%
“…These checkpoint expressed on T-cells was found in peripheral blood and tumor tissue have limited ability to effectively eliminate tumors, have gained considerable attention and PD-1 expression on peripheral blood T-cell subsets correlates with prognosis in non-small cell lung cancer [88,89]. These molecules were found expressed on CIK cells [60]. The majority of these molecules, except BTLA were increased during CIK cells culture.…”
Section: Immune Checkpoint In Nsclc Patientsmentioning
confidence: 99%
“…Recent research has led to an improved understanding of the immune system resulting in better therapeutic strategies. The initiation of the immune cascade is a multifaceted, multistep process 24. The major histocompatibility complex (MHC), expressed on the surface of antigen-presenting cells (APCs), assists with internalizing and identifying tumor antigens.…”
Section: Lung Cancer Immunologymentioning
confidence: 99%